Peningkatan Kemampuan Peserta Didik terhadap Baca Tulis Al-Qur'an melalui Guru Pendidikan Agama Islam - Rinah Rinah (Journal on Education, 2023)
Schools have an important role to paint the intellect and spirituality of a child. The spirituality of a student can be well formed by reading the Qur'an, because the Qur'an not only teaches how to worship Allah but also how to be civilized with other living things.This study aims to examine the competence of Islamic Religious Education teachers at SMP Negeri 4 Pekanbaru in improving students' ability to read and write the Qur'an, the supporting and inhibiting factors as well as the solutions offered to improve students' ability to read and write the Al-Qur'an. an. The subjects in this study were students of SMP Negeri 4 Pekanbaru. The method in this study used descriptive qualitative. Data was collected through observation, documentation and interview methods. Interviews were conducted with 4 teachers at SMP Negeri 4 Pekanbaru. The results of the study show that 1) the competence of PAI teachers at SMP Negeri 4 Pekanbaru is realized by making a lesson plan outlined by the government using the independent curriculum form, the learning method used is the wahdah bil kitabah method and the iqra method; 3) the supporting factors for the implementation of PAI learning consist of teachers, students, and the school environment; 4) The obstacles encountered were the learning time to read and write the Al-Qur'an which was short, only 2 hours of lessons, the lack of learning media to read and write the Al-Qur'an and the background of the students; 5) The solution offered is the Al-Qur'an reading and writing learning method which is applied must consider the characteristics of students and the use of audio-visual learning methods.